2022
DOI: 10.1038/s41598-022-10769-w
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology of iridoid glycosides from Eucommia ulmoides Oliver against osteoporosis

Abstract: Eucommia ulmoides Oliver is one of the commonly used traditional Chinese medicines for the treatment of osteoporosis, and iridoid glycosides are considered to be its active ingredients against osteoporosis. This study aims to clarify the chemical components and molecular mechanism of iridoid glycosides of Eucommia ulmoides Oliver in the treatment of osteoporosis by integrating network pharmacology and molecular simulations. The active iridoid glycosides and their potential targets were retrieved from text mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 87 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…The overlapped gene symbols, referred to as targets of zingiber zerumbet in IPF were then obtained by uploading the component gene and the disease gene using the Venny 2.1 (https://bioinfogp.cnb.csic.es/tools/ venny) duplication method mapping tool. 37…”
Section: Targets Excavatingmentioning
confidence: 99%
See 1 more Smart Citation
“…The overlapped gene symbols, referred to as targets of zingiber zerumbet in IPF were then obtained by uploading the component gene and the disease gene using the Venny 2.1 (https://bioinfogp.cnb.csic.es/tools/ venny) duplication method mapping tool. 37…”
Section: Targets Excavatingmentioning
confidence: 99%
“…The Compound-Target-Pathway network was built by merging the Compound-Target and Pathway-Target networks in order to better understand the interactions among the phytomolecules, targets, and pathways. 37 Based on the pathway analysis, the top 20 key pathways were considered with the enriched hub targets to build and analyse the pathway-target network. The relationship between the primarily screened compounds with their top subnetwork targets was developed and analysed.…”
Section: Compound-target-pathway Networkmentioning
confidence: 99%
“…It was found that ethanol extracts from Eucommiae Cortex alleviated the inflammatory response through the OPG/RANK/RANKL and NF-κB pathways to delay the destruction of intraarticular cartilage and bone. Zhang et al (2021) ; Wang et al (2022a) ; Zhang et al (2014) The ethanol extracts and polysaccharides from Eucommiae Cortex increased the coefficient of the thymus and spleen and improved the clearance ability and phagocytosis ability of peritoneal Mφs in mice. Qiu et al (2008) ; Ye et al (2015) Osthole may restore BMSC-mediated T-cell migration and apoptosis by stimulating the expression of Fas/FasL, enhancing the immune activity of BMSCs in healthy or inflammatory microenvironments to treat OP ( Yu et al 2021 ), and downregulating c-Scr, β3-integrin and OC genes to inhibit OC formation and bone resorption.…”
Section: Immunoregulation Mechanisms By Which Tonifying Kidney-yang H...mentioning
confidence: 99%
“…GEN becomes a research agent in preclinical studies related with diseases [ 20 ]. GEN has been shown to improve osteoporosis [ 21 ]. ATP-binding cassette transporter A1 (ABCA1) is a carrier for the intracellular cholesterol out of the cytoplasm [ 22 ].…”
Section: Introductionmentioning
confidence: 99%